Peningkatan interaksi sosial dan hasil belajar melalui media permainan ular tangga di sekolah dasar - Ulfatu Solichah; Insanul Qisti Barriyah; Ana Fitrotun Nisa (LP2M Universitas Sarjanawiyata Tamansiswa, 2025)
Language proficiency in Indonesian comprises four core skills: listening, reading, speaking, and writing. These foundational skills are essential across all educational levels, from elementary to tertiary education. One effort to enhance the success of Indonesian language learning is through the application of effective, creative, active, and enjoyable instructional innovations. Proverbs, which convey figurative meanings, are often difficult for students to understand and interpret. This study aims to examine the effectiveness of using an educational Snakes and Ladders game to improve sixth-grade primary students’ learning outcomes in understanding proverbs. A descriptive qualitative method with purposive sampling was employed. The participants consisted of 48 sixth-grade students from two primary schools in Temanggung Regency. The results indicated that the Snakes and Ladders game significantly increased students’ motivation and academic achievement in learning proverbs. The use of the game provided a more engaging, varied, and participatory learning experience. Integrating this instructional medium into proverb instruction is expected to contribute positively to the quality of education and student learning outcomes.